Brødre i ånden. Professionalisering af biblioteksfaget som afspejlet i breve mellem Svend Dahl og Wilhelm Munthe - Larsen, Svend (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
Svend Larsen: Kindred souls. Svend Dahl and Wilhelm Munthe on the professionalisation of academic librarianship Svend Dahl (1887–1963) and Wilhelm Munthe (1883–1965) were prominent figures in Scandinavian and international librarianship in the first part of the 20th Century. From 1922–1953, Munthe was head of Oslo University Library which was also Norwegian national library. Internationally, he is known as the author of American Librarianship from a European angle. An attempt at an examination of policies and activities (1939) and as president of the international library federation IFLA (1947–1951). Svend Dahl was head of Copenhagen University Library 1925–1943 and head of the Royal Library and national librarian 1943–1952. Internationally, he is known for his many publications such as the History of the Book (Danish, English, French, German, Spanish and Swedish editions). Dahl and Munthe exchanged just under 200 letters between 1916 and 1953. These letters reveal their views concerning academic librarianship and the need and the ways to professionalise it. In the exchange of letters, the two men also discussed other topics, such as education, internationalisation, and the separation of library and university.